Pengembangan Sistem Informasi Konseling Mahasiswa Fakultas Ilmu Komputer Universitas Brawijaya Menggunakan Metode Rational Unified Process (RUP) - Adhitira Febrieztha Ramadhan; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Solving problems through guidance and counseling (GC) service with counseling is one of the way that Computer Science Faculty Brawijaya University's students do. But there are many students who haven't use the service. Besides, the GC service hasn't had an information system that can manage the data counseling and the psycotest. Almost all of the activities are still using conventional method, it's caused the data counseling and the psycotest process become slow. The GC service needs a system that can connect the students and the counselor to do counseling indirectly, and it can manage the data counseling and the psycotest. Rational Unified Process (RUP) is a developing method that is choosed to be used in this research because it can control the changing from the system, and it has a good documentation. RUP is used by doing inception, elaboration, contruction, and transition. The result test that has got is all of the functional requirements are all valid with 100% score of validation. Then, the result of compatibility test shows that the system has a good compatibility, The user acceptance testing also provides that the students has score 81,3% with the system's acceptance, and the counselor has score 88,57% with the system's acceptance too. It means that the system is accepted by both the students and the counselor well.